The Analysis of Leadership and Organizational Culture on Employee Performance through Work Motivation as an Intervening Variable - Jumawan; Hapzi Ali; Ni Nyoman Sawitri; Dewi Puspaningtyas Faeni (International Journal of Global Sustainable Research, 2023)
This study aims to determine the effect of leadership and organizational culture on employee performance through work motivation as an intervening variable. The population in this study was Executing Examiners at one of the Bekasi Customs and Excise Offices, totaling 143 people. Based on the Slovin formula, the number of samples taken was 60 people. The sampling technique in this study uses probability sampling, with the simple random sampling method. The data analysis technique uses the Partial Least Square (PLS) approach. The results showed that: 1) Leadership has a direct and significant effect on work motivation, 2) Organizational culture has no direct effect on work motivation; 3) Leadership, organizational culture, and work motivation have a direct and significant effect on employee performance; 4) Work motivation variable is able to mediate the influence of leadership on employee performance; 5) Work motivation variable is not able to mediate the influence of organizational culture on employee performance.